MENGUSUNG KEMBALI KHAZANAH IDENTITAS BUDAYA BANGSA - Husamah, Husamah (Jurnal Bestari, 2009)
Indonesians are actually representation of rich nation because they have many cultures with various diversities. On the other hand, the fact is that there are so many cultures have lost, entirely disappeared, or stolen by others. It is because we are remiss to behave properly on the cultures and carry out them. Therefore, it needs institutional approach in the form of government?s concrete steps and reinforcement on education?s role.